Manajemen Rehabilitasi Fisioterapi pada Bayi dengan Spastic Cerebral Palsy: Laporan Kasus - Devi Rifqi Ayuningtias; Wahyuni Wahyuni; Ika Hayati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Cerebral palsy (CP) is a non-progressive motor disorder caused by early brain injury. The spastic type is characterized by increased muscle tone and limited voluntary movement, often leading to delayed gross motor development in children. This case report aims to describe physiotherapy management in a spastic CP infant and evaluate the response after two weeks of intervention. The patient was a 10-month-old male infant (corrected age 8 months 19 days) with a history of prematurity, neonatal asphyxia, and diagnosed with spastic CP. Physiotherapy interventions included neurosensory stimulation, Bobath positioning, head and trunk control training, and a home program provided to the parents. Evaluation was conducted through clinical observation and the Hammersmith Infant Neurological Examination (HINE). After two weeks of therapy, the patient showed minor improvement in head control and reduced head lag, but no significant development in gross motor skills such as rolling or sitting. HINE score was 34, indicating a non-ambulatory prognosis. Short-term physiotherapy management in spastic CP can support early postural control, but long-term intervention and strong family involvement are essential to achieve optimal motor development.